PENGARUH PENGALAMAN, KOMPETENSI, DAN KOMPENSASI TERHADAP KINERJA PEKERJA UMKM DI PASAR LAMA TANGERANG DENGAN MOTIVASI SEBAGAI PEMEDIASI - Harijanto Ratana; Toni Yoyo (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
MSMEs play a crucial role in Indonesia’s economy but still face challenges related to human resource quality, such as experience, competence, and compensation, which affect employee performance. This study examines the influence of experience, competence, and compensation on the performance of MSME workers in Pasar Lama Tangerang, with motivation as a mediating variable. Using a quantitative causal research approach, data were collected through a Likert-scale questionnaire from 300 respondents with diverse backgrounds, and analyzed using SEM with SmartPLS. The results show that all variables have T-statistics above 1.96 and P-values below 0.05. Experience, competence, and compensation significantly and positively impact performance, both directly and through motivation as a mediator. The study suggests improving competency training, offering fair compensation, and managing work experience to enhance worker performance. Future research is encouraged to explore additional variables.